Reasons for formula feeding among rural Bangladeshi mothers: A qualitative exploration - Rahman, Atiya; Akter, Fahmida (PLOS ONE, 2022)
This article was published in the PLoS ONE [© 2019 Rahman, Akter. This is an open access article distributed under the terms of the Creative Commons Attribution License ] and the definite version is available at: https://doi.org/10.1371/journal.pone.0211761 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0211761